(untitled) (Journal of Academic Research, 2023)
The study aims to identify the impact of integration between information technology governance and the added value of internal audits on reducing the risks of electronic accounting information systems in industrial companies operating in Misurata. To achieve the aims of the study، the descriptive analytical approach was relied upon، and the questionnaire was used to collect information، which was distributed to the study sample in industrial companies operating in Misurata، which included internal auditors، accountants، IT staff، and general managers to obtain the necessary information، where these data were analyzed using the SPSS statistical analysis program and testing hypotheses. The findings of the study indicate that the participants of the study believe that there is a statistically significant impact of the integration between information technology governance and the added value of internal audit on reducing the risks of electronic accounting information systems in industrial companies operating in Misurata، there is a significant impact of the added value of internal audit on reducing the risks of electronic accounting information systems in industrial companies operating in Misurata، and there is a statistically significant impact of information technology governance on reducing the risks of electronic accounting information systems in industrial companies operating in Misurata. Keywords: information technology governance، adding value to internal audits، risks of electronic accounting information.